South Caucasus in Motion : Economic and Social Mobility in Armenia, Azerbaijan and Georgia - Tiwari, Sailesh (World Bank, Washington, DC, 2018)
This paper presents a comprehensive analysis of economic and social mobility in countries in the South Caucasus by complementing available household survey data in each of the countries in the subregion with other sources, such as the Life in Transition Survey (2016). The first part of the paper -- concentrated on intragenerational mobility -- finds that despite progress made in reducing poverty over the past decade, there appears to be a significant amount of churning around the poverty line. Moreover, in Georgia and Armenia, roughly one in eight individuals lived in a state of chronic poverty in 2015, and in the case of Georgia, chronic poverty is not an exclusive phenomenon for rural areas. In addition, although social programs have provided a lifeline for the chronic poor, the ability to tap into labor market opportunities has been the ticket out of poverty. The second part of the paper expands the analysis to intergenerational or social mobility. The main findings are that (1) a higher proportion of the population in this subregion considers their pre-transition family life and the lives of their parents when they were of similar age as appropriate benchmarks to evaluate their current economic situations in comparison with the other transition countries, and (2) over half of the Georgian and Armenian population disagreed with the statement that asked their views on having a better in life than their parents, aligning with the “growing but unhappy” trend that has been reported for the region.